Albums from the Former H. Destailleur’s Collection in the State Hermitage: A Historical Context and Some Problems of Interpretation - Efimova, Elena A. (Actual Problems of Theory and History of Art, 2013)
Three albums of 16th c. architectural drawings from the former collection of H. Destailleur (now in the Scientific Library of the State Hermitage museum) represent an interesting ensemble, almost unknown to art historians. The article highlights the problem of their attribution, dating and connections with the architectural drawings of the mid-16th c. The most attention is given to the specificity of the albums genre — the architectural model books. The article analyses of this group of architectural drawings in a wide historical context and defines their place in the progress of architectural theory and practice of the Renaissance.
Keywords: architectural drawings; studies of antique monuments; model books; order details; prototypes; “genetic groups”